In touch with the user - Seguine, Ryan (Electronics Weekly, 2005)
In the case of the Cypress CapSense, designers can control multiple capacitive touch sensing applications such as buttons, sliders, and touchpads and noncapacitive touch sensing elements, such as LEDs or LCDs, with the same device, simplifying the schematic and decreasing the bill of material costs. CapSense uses public domain technology so it is not subject to patent issues.